PENGARUH PENGGUNAAN FERMENTASI DAN AMONIASI KULIT SINGKONG DALAM RANSUM TERHADAP PERTAMBAHAN BOBOT TUBUH DAN KONVERSI PAKAN PADA TERNAK DOMBA JANTAN - Yuswan Jaya; Muhtarudin Muhtarudin; Kusuma Adhianto; Erwanto Erwanto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This research intended to determine the effect of using fermented and ammoniated of cassava peel on body weight gain and feed convertion in male sheep. This research was conducted in June until August 2019 in a cage unit located in the Animal Husbandry Department, Agriculture Faculty, Lampung University. The research used Completely Randomized Design with 3 treatments and 3 replications. Experimental unit of this experiment were nine sheeps. The treatment used were P0 (Ration + 15% cassava peel without processing), P1 (Ration + fermented cassava peel), and P2 (Ration + ammoniated cassava peel). Variable in this study were feed intake, body weight gain, and feed conversion. The data obtained were analyzed for variance with significance level 5%. The results showed that the use of fermented and amoniated of cassava peel was not significant (P>0,05) on feed intake, body weight gain, and feed conversion. Conclusion of this research is that fermented and ammoniated of cassava peel use in ration did not significantly increase body weight of sheep. Key words: Amoniation, Body weight gain, Cassava peel, Feed convertion rate, Fermentation